Research on Curriculum System for Academic Doctoral Training in Teacher Education: A Case Study of Michigan State University - ZHAO Ying; LIU Yanren (Jiaoshi jiaoyu xuebao)
The academic doctoral program in teacher education of Michigan State University (MSU) aims to cultivate outstanding scholars and educationalists who possess a deep understanding of education and are committed to educational reform. To achieve this goal, the program constructed a high-quality "4+1" modular curriculum system. The number "4" refers to professional seminar courses focusing on the cultivation of critical thinking, core courses centering on teacher professional development, educational research methodology courses emphasizing research-based learning, and academic practice courses adopting a problem-oriented approach. The number "1" refers to the graduate certificate programs designed to enhance professional skills. This curriculum system is distinctly characte-rized by research-based learning and problem-oriented approaches, combination of educational know-ledge and skills, emphasis on interdisciplinary training, consistent curriculum structure, and teacher professional development, which highlights the pursuit of high-quality teacher education.